Comparisons of spatiotemporal parameters of 100-m sprint among elite-, sub-elite and non-elite amputee sprinters - Hobara, H.; Hashizume, S.; Kobayashi, Y.; Mochimaru, M. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
We investigated differences of the spatiotemporal parameters in a 100-m sprint among elite, sub-elite, and non-elite sprinters with a unilateral transtibial amputation. Using publicly available Internet broadcasts, we analyzed 125, 19, and 33 records from 30 elite, 12 sub-elite, and 22 non-elite sprinters, respectively. Average speed, step frequency, and step length were calculated Average speed was greatest in elite sprinters, followed by the sub-elite and non-elite groups. Although there was no significant differences in average step frequency, the average step length was longest in elite sprinters, followed by the sub-elite and non-elite groups. These results suggest that the differences in sprint performance between the three groups is mainly due to the average step length rather than step frequency.